Are Gill Rackers Involved in Taste Perception and Food Ingestion for Gobio carpathicus (Vladykov, 1925)? A Debate Sustained by Histological Arguments - Maria-Catalina MATEI-LATIU; Calin LATIU; Vasile RUS; Adrian Florin GAL (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Veterinary Medicine)
The feeding behaviour of fish is drastically influenced by food availability and dietary preferences. In omnivorous fish, chemoreception plays an important role in feeding and morphological adaptations may be observed in several regions of the body. However, it is not clearly known if the fish need to feel the taste before swallowing the food. The present study aims to describe the receptors for taste perception and their distribution at the level of the gill rackers, underlining their importance in the food sorting behaviour. Paired gills were harvested from Carpathian gudgeon fish Gobio carpathicus Vladykov, 1925 and immersed in 10% buffered formalin. The samples were processed according to the current paraffin embedding technique and stained with Goldner’s trichrome method. The obtained results suggest that the Carpathian gudgeon presents, up to a point, the common gill morphology. However, on the pharyngeal face of the gills, more exactly on the gill rackers, are present several structures with an onion-like shape, disposed through the surface of the epithelium. Those elements consist of sensorial cells, sustained by sustentacular and basal cells, forming a taste bud. Due to their disposition on the inner surface of the gills, those structures may act like a sorter, enhancing the rackers sieve activity. In conclusion, the histological findings suggest that the Carpathian gudgeon, a common omnivorous fish, may use taste reception at the level of the gill rackers before swallowing the food.